Trip Generation Models for Transportation Impact Analyses of Shopping Centers in Croatia - Deana Breški; Biljana Maljković; Mihaela Senjak (Infrastructures)
For effective transportation planning, land use, travel behavior, and infrastructure capacity should be optimized to support sustainable urban growth and reduce congestion. Every new site development generates traffic volume, which can affect the quality of traffic flow in the surrounding road network. Therefore, trip generation, which predicts future travel demand, is a crucial step in the traditional four-step transportation model. In this context, the main objective of this study is to develop a model for estimating vehicle trip generation due to the construction of a shopping center, which is a significant traffic generator. The survey was conducted in Split (Croatia) at five existing locations, and linear regression analysis was used to develop models for different time periods. The results indicated that vehicle trips are strongly correlated with the gross floor area of shopping centers, with a high coefficient of determination. Additionally, this study presents a comparison of measured traffic volumes with estimates using ITE Trip Generation Manual equations. The findings suggest that these vehicle trip estimates should be reduced by approximately 40%. Since no previous studies have been conducted on the impact of land use on trip generation in the Republic of Croatia, the developed models represent a first step in creating a database that should be expanded with new data. Estimating the traffic generated by a new site development is a crucial component of traffic management, as it helps planners and engineers assess its impact on the surrounding road network and implement necessary measures to ensure efficient and safe traffic flow.